Associations between Digital Literacy and Executive Functions in College Undergraduates - Tabullo, Ángel Javier; Saux, Gastón; Grasso, Lina (Psykhe, 2024)
Digital literacy can be defined as a set of skills for searching, accessing, navigating, integrating, and evaluating the reliability of information on the internet, mainly in written form. The present study aimed to examine the contribution of executive function skills (inhibition, cognitive flexibility and working memory) to performance on a digital literacy assessment tool in college undergraduates. Eighty-five Argentinean university undergraduates (56 female, mean age 20.34 ± 4.6 years) completed a digital literacy test and a computerized executive functions battery. After controlling for vocabulary scores and sociodemographic factors, cognitive flexibility was the main predictor of digital literacy scores. In particular, it was associated with information search and integration task performances. Visuospatial working memory predicted information search scores and inhibition correlated positively with reliability evaluation tasks. Our results indicated: 1) a general involvement of cognitive flexibility in digital literacy, possibly reflecting the need to shift between multiple documents, reading or navigation strategies; 2) a specific link between visuospatial working memory and information search, which might be indicating a spatial processing load related to hyperlink navigation; and 3) a possible involvement of inhibition in the evaluation of web documents, which may contribute to the suppression of irrelevant information.